Non-axisymmetric equilibrium and stability using the ELITE stability code. (11th October 2019) - Anastopoulos-Tzanis, M.S.; Dudson, B.D.; Ham, C.J.; Hegna, C.C.; Snyder, P.B.; Wilson, H.R.
Abstract: Linear perturbation theory is used to model the ideal magnetohydrodynamic stability of tokamak equilibria under the application of external 3D magnetic perturbations (Hegna 2014 Phys. Plasmas 21 072502). We use the ELITE code (Wilson et al 2002 Phys. Plasmas 9 1277) to produce both a linear plasma response, as well as the linear axisymmetric toroidal eigenmodes which are used as basis functions for the 3D perturbative stability analysis. The symmetry breaking produces coupling of modes with different toroidal mode number, n, leading to modification of the linear growth rates, and poloidal localisation of the non-axisymmetric peeling–ballooning mode at sufficiently large applied field.